The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.yexcr.2019.111565
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell modulation of cardiomyocyte gene expression

Abstract: WB Western blot WGA Wheat germ agglutinin β-MHC -Myosin heavy chain 2013, Fredriksen et al., 2001). Kidney disease is commonly found in heart failure (HF) patients (Grande et al., 2017). It was found that GFR is associated with the degree of cardiac diastolic dysfunction and adverse clinical outcomes (Jain et al., 2017). A recent nationwide population-based cohort study showed that heart failure patients have a higher risk of developing dementia (Adelborg et al., 2017). Studies also revealed post-mortem that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…As reviewed in the introduction, EndMT is an important cellular phenomenon that induces microvascular dysfunction and acts as an important source of myofibroblasts that directly affect cardiac function in DCM. 23,24 EndMT has also been implicated in the pathogenesis of diabetic fibrosis; for instance, Wang et al reported that HG levels can induce EndMT in human umbilical vein endothelial cells, including changes in corresponding protein expression and morphology. 25 These evidences indicate the sensitivity of endothelial cells to hyperglycemia, but there was no direct evidence to support the EndMT in CMECs caused by T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed in the introduction, EndMT is an important cellular phenomenon that induces microvascular dysfunction and acts as an important source of myofibroblasts that directly affect cardiac function in DCM. 23,24 EndMT has also been implicated in the pathogenesis of diabetic fibrosis; for instance, Wang et al reported that HG levels can induce EndMT in human umbilical vein endothelial cells, including changes in corresponding protein expression and morphology. 25 These evidences indicate the sensitivity of endothelial cells to hyperglycemia, but there was no direct evidence to support the EndMT in CMECs caused by T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ECs can also synthesize and secrete a variety of bioactive cytokines. This endothelial paracrine activity, known as endothelial microenvironment function, is important for organ maintenance and tissue repair and regeneration (He et al, 2017; Jiang et al, 2019; Kivela et al, 2019).…”
Section: Cell Therapy For Heart Regenerationmentioning
confidence: 99%
“…For example, EC have been shown to protect cocultured CM from hypoxia-reoxygenation injury via both hypoxia-inducible factor (HIF1α) ( Leucker et al, 2011 ) and NO signaling ( Leucker et al, 2013 ). Similarly, transwell coculture systems have implicated EC-derived paracrine factors in control of CM cytoskeletal organization ( Zhang et al, 2015 ) and natriuretic peptide expression ( Jiang et al, 2019 ).…”
Section: Current Models Of Endothelial Dysfunction In Cardiac Develop...mentioning
confidence: 99%